Pengaruh Hedonic Shopping Motivation Dan Shopping Lifestyle Terhadap Impulse Buying - Mujianah, Siti; Fikri, Abdullah; Yakub, Rizky; Sanjaya, Vicky F. (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The emergence of the influence of current trends, promotions, and discounts, as well as advertising offers play a major role in shaping hedonic shopping motivation and shopping lifestyle, so that these influences create the urge to buy without careful consideration. Thus, the goal is to identify and measure the influence of Hedonic Shopping Motivation and Shopping Lifestyle on Impulse Buying of Raden Intan State Islamic University students in Lazada.co.id and helps in detailing how much the independent variable is related to or affects the dependent variable. This study uses quantitative methods by collecting primary data through the distribution of questionnaires online using the Google Form platform. The population focus of this study is students of the state Islamic University of Raden Intan Lampung who have made purchases in Lazada.co.id, with a sample of 91 respondents and selected through non probability sampling. Especially purposive sampling techniques, which allow researchers to select samples based on certain considerations, so as to ensure that the selected sample represents the relevant variation in the population. This study used the test tool SmartPLS 4 for windows. The results showed that Hedonic Shopping Motivation showed a positive but not significant effect on Impulse Buying. Meanwhile, Shopping Lifestyle shows a positive and significant influence on Impulse Buying. Thus, Shopping Lifestyle has a dominant role in triggering Impulse Buying compared to Hedonic Shopping Motivation. Abstrak Munculnya pengaruh tren terkini, promosi, dan diskon, serta tawaran iklan berperan besar membentuk motivasi belanja secara hedonis dan gaya hidup belanja, sehingga pengaruh tersebut menciptakan desakan untuk membeli tanpa pertimbangan matang. Sehingga, tujuannya untuk mengidentifikasi dan mengukur pengaruh Hedonic Shopping Motivation dan Shopping Lifestyle terhadap Impulse Buying Mahasiswa Universitas Islam Negeri Raden Intan Lampung pada Lazada.co.id dan membantu dalam merinci seberapa besar variabel bebas tersebut berhubungan ataupun mempengaruhi variabel terikat. Penelitian ini menggunakan metode kuantitatif dengan mengumpulkan data primer melalui distribusi kuesioner secara online menggunakan platform Google Form. Fokus populasi Penelitian ini yaitu Mahasiswa Universitas Islam Negeri Raden Intan Lampung yang telah melakukan pembelian di Lazada.co.id, dengan sampel sebanyak 91 responden dan dipilih melalui cara non probability sampling. Khususnya tehnik purposive sampling, yang memperkenankan peneliti untuk memilih sampel berdasarkan pertimbangan tertentu, sehingga dapat memastikan bahwa sampel yang dipilih mewakili variasi yang relevan di dalam populasi. Penelitian ini menggunakan alat uji SmartPLS 4 for windows. Hasil penelitian menunjukkan bahwa Hedonic Shopping Motivation memiliki pengaruh positif namun tidak signifikan terhadap Impulse Buying. Sementara itu, Shopping Lifestyle menunjukkan pengaruh positif dan signifikan terhadap Impulse Buying. Dengan demikian, Shopping Lifestyle memiliki peran dominan dalam memicu Impulse Buying dibandingkan dengan Hedonic Shopping Motivation.